PENGEMBANGAN BUKU SISWA TERPADU TIPE JARINGAN KERJA TERINTEGRASI PENDEKATAN ILMIAH DI SD KELAS IV - Kharisma Eka Putri (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2017)
Research of the teaching material development of networkedÃƒâ€šÃ‚Â with scientific approach was proposed to determine: the feasibility of student book developed andÃƒâ€šÃ‚Â students responses. To attain these objectives, it had been research that started by preparation of student books, followed by try out of the teaching material in the integrated science learning. The research was conducted on a class IV student SD Negeri1 Ngampel Kediri many as 12 students. The teaching material development model used was 4D. However, in this study was limited until to the development stage. Data collect method in this experiment is validation and questionnaire. The data ofÃƒâ€šÃ‚Â research showed that the student book developed was feasible to use suitable with expert validation and validation ofÃƒâ€šÃ‚Â the student book readability. The result obtained from validation of student books 3,62. Mean while, the readability of the studentÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢s book gets a percentage ofÃƒâ€šÃ‚Â 83,33 with a very strong criterion. The results ofÃƒâ€šÃ‚Â questionnaire analysis responses showed that students in integrated science type networked, with Scientific ApproachÃƒâ€šÃ‚Â teaching were students responded positively to that learning.